DEVELOPING STUDENTS’ CREATIVITY AND COHERENCE IN NARRATIVE WRITING THROUGH PICTURE: A CLASSROOM ACTION RESEARCH AT MAN 1 PROBOLINGGO - Nafisah, Lailatun; Tirmidi, Tirmidi; Rohmaniyah, Sheila (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This classroom action research (CAR) investigated the use of the picture series technique to enhance narrative writing creativity and coherence among 10 twelfth-grade EFL students at MAN 1 Probolinggo. Conducted in two cycles, data were collected through observations, writing tests, and interviews. Findings revealed a significant improvement in students’ creativity (from 67.8 to 82.4) and coherence (from 75.1 to 84.7). Qualitative results indicated greater motivation, confidence, and engagement. The study concludes that visual prompts help students conceptualize ideas, structure narratives logically, and perceive writing as a creative process. Pedagogically, this research contributes to EFL writing instruction and multimodal learning, highlighting visual-based techniques as effective for enhancing both cognitive and affective learning dimensions